Discharge against Medical Advice (DAMA) from an Emergency Department of a Tertiary Care Hospital in Saudi Arabia - Ashraf El-Metwally; Nesreen Suliman Alwallan; Ali Amin Alnajjar; Nida Zahid; Khalid Alahmary; Paivi Toivola (Emergency Medicine International)
Background. The discharge against medical advice (DAMA) in the Emergency Department (ED) is an issue of great concern because it may result in adverse consequences at a later stage. The reported worldwide prevalence of DAMA ranges from 0.07 to 20% for emergency admissions. The outcomes of DAMA can have significantly damaging effects, causing possible relapses of disease, readmission, and increases in medical costs for the patient. Therefore, it is imperative to identify the predictors of DAMA in ED. Methods. It was a cross-sectional study. The medical records used were those of all the patients (n = 11513) admitted to the Emergency Department (ED) of King Abdullah Bin Abdulaziz University Hospital (KAAUH) in Riyadh, Saudi Arabia, between 2017 and 2018. A thorough analysis was performed using IBM SPSS Statistics version 22. Descriptive statistics were reported for quantitative and categorical variables and assessed by independent t-test/chi-square/ANOVA (analysis of variance), where appropriate. Unadjusted and adjusted odds ratios with their 95% CI (confidence interval) were reported by performing logistic regression. A p value of ≤0.05 was considered statistically significant throughout the study. Results. The prevalence of DAMA in our study was 1%. In a multivariable analysis, after adjusting for the other covariates, we observed a significant interaction between age and gender. It was observed that the odds of DAMA for ≤40-year-old males were 3.12 times higher than those of a ≤40-year-old female (p value < 0.1). To further investigate this interaction, men and women were modeled separately in multivariable models using the same covariates. We found that, for men, the effect of age (≤40 years) was significant (OR = 3.94, 95% CI 1.31–11.80, p=0.014), while, for women, the effect of age (≤40 years) was not as pronounced (OR = 1.27, 95% CI = 0.66–2.42, p=0.27). Conclusions. Our study concluded that DAMA was more likely among younger male patients (≤40 years of age). Most of the patients with DAMA were presented to the urgent care of the Emergency Department. We recommend that patients be given some financial support to bear the expenses of the hospital stay from the healthcare facility or from the state. Future studies should assess the socioeconomic status of the patients and estimate the cost that is incurred by the patients.